Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1142/s1793626812300022
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Materials and Conductors: Fabrication and Limiting Parameters

Abstract: Superconductivity is the technology that enabled the construction of the most recent generation of high-energy particle accelerators, the largest scientific instruments ever built. In this review we trace the evolution of superconducting materials for particle accelerator magnets, from the first steps in the late 1960s, through the rise and glory of Nb-Ti in the 1970s, till the 2010s, and the promises of Nb 3 Sn for the 2020s. We conclude with a perspective on the opportunities for high-temperature superconduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 112 publications
1
42
0
Order By: Relevance
“…It is found that at least down to the 31.6 mm diameter coil-section there is only a small gradual reduction that is due to the small intrinsic and reversible strain-dependence that is typical for Bi-based superconductors [6, 27, 31, 36]. Included in figure 13 are the I c values from the single- and double-bent samples at the 56 mm position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that at least down to the 31.6 mm diameter coil-section there is only a small gradual reduction that is due to the small intrinsic and reversible strain-dependence that is typical for Bi-based superconductors [6, 27, 31, 36]. Included in figure 13 are the I c values from the single- and double-bent samples at the 56 mm position.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing this current-density with the performance of modern high-current LTS conductors [4, 5, 6] (figure 1), it is clear that 23.5 T is at the limit of what is presently achievable with LTS. The key origin of this performance limitation is intrinsic and determined by the upper critical field ( B c2 ) of Nb 3 Sn of 30 T [7].…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting materials and cables are discussed elsewhere in this volume [10]. It is worthwhile here to report on the practical materials that can be used for magnets, making reference to Fig.…”
Section: Superconductor Load Line and Marginsmentioning
confidence: 99%
“…Coupling currents in strands and cables flow in loops formed among the superconducting filaments, with a return path across the wire matrix, or the strand contacts [10,13]. The amount of coupling depends on the geometry of the current loop, which is made as small as possible by twisting, and on the resistivity of the matrix or the strand contacts.…”
Section: Field Quality and Harmonic Contentmentioning
confidence: 99%
“…There may, however, be only limited interest in a tape-form conductor given the competition from higher T c tape-form YBCO coated conductors (T c $ 90 K) and tapes of (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O 10 (Bi2223) (T c $ 100 K). As a round wire, however, there are many attractions of a 38 K superconductor like K-doped Ba122 with almost no electronic anisotropy (H c2 anisotropy $1.1) and H c2 (0) $ 90 T, provided that the in-field current density can be raised to $5 Â 10 4 A cm À2 in the 10-30 T range at 4.2 K. 17,18 It is therefore very important to understand if the properties of present Ba122 polycrystals are limited by intrinsic GB properties or by extrinsic factors such as impurity segregation or chemical composition variations that take GB compositions far away from the bulk compositions. Transmission electron microscopy (TEM) has revealed oxide phase formation at the GBs in a polycrystalline (Sr 0.6 K 0.4 )Fe 2 As 2 superconductor, 19 but slight compositional changes and segregation of lighter atoms on a smaller length scale can be difficult to detect and quantify by analytical TEM, especially due to the rapid degradation of electrontransparent samples, which has prevented accurate quantitative analyses of GBs of the higher J c K-doped 122 samples.…”
mentioning
confidence: 99%